BENTUK SIMBOLIS ESTETIKA JAWA PADA PERTUNJUKAN WAYANG PURWA - Robby Hidajat (Institut Seni Indonesia Surakarta, 2009)
Javanese aesthetics is closely related to Javanese performing art, especially wayang. Due to that, â€œJavanese aestheticsâ€ can be understood through the performing art in practice. The lesson that can be obtained is morality that can be completely understood in a cosmic sphere the nature of which is paradoxicalÂ and opposing. It is still possible to carry out an in-depth study to Javanese aesthetics and this preliminary study puts an emphasis on symbolic aspects on wayang purwa performance. Key words : wayang, aesthetics, paradoxical, philosophyÂ